Synthesis and coordination studies of 5-(4′-carboxyphenyl)-10, 15, 20-tris(pentafluorophenyl)porphyrin and its pyrrolidine-fused chlorin derivative. (26th February 2018) - Almeida, José; Silva, André M. N.; Rebelo, Susana L. H.; Cunha-Silva, Luís; Rangel, Maria; de Castro, Baltazar; Leite, Andreia; Silva, Ana M. G.
Abstract : An efficient strategy was developed to obtain carboxyphenyl porphyrin, chlorins and metal complexes, with potential applications in photonics and biology. Abstract : The introduction of a carboxylate function into porphyrins allows a variety of modifications, including coordination and conjugation, which are central to enhance the efficiency of macrocycles in photonic materials and biological applications. Herein, a synthetic strategy to obtain 5-(4′-carboxyphenyl)-10, 15, 20-tris(pentafluorophenyl)porphyrin and its pyrrolidine-fused chlorin derivative was developed by the 1, 3-dipolar cycloaddition of a carbomethoxyphenyl substituted porphyrin with an azomethine ylide, followed by hydrolysis under thermal acidic conditions. The 1, 3-dipolar cycloaddition of the carbomethoxyphenyl porphyrin with N -methyl nitrone was also performed to give an isomeric mixture of isoxazolidine-fused chlorins, revealing lower selectivity and lower yields; in addition, retrocycloaddition of the isoxazolidine-fused chlorins was observed under the hydrolysis conditions. The resulting carboxyphenyl macrocycles were characterized using 1 H and 19 F NMR, ESI-MS and SC-XRD for 5-(4′-carboxyphenyl)-10, 15, 20-tris(pentafluorophenyl)porphyrin. In order to study the influence of coordination to a metal ion on the electronic properties of carboxyphenyl substituted porphyrins, a series of metal complexes of 5-(4′-carboxyphenyl)-10, 15, 20-tris(pentafluorophenyl)porphyrin and its pyrrolidine-fused chlorin derivative were synthesized by microwave-mediated metallation with Fe(iii ), Cu(ii ) and Zn(ii ) salts. EPR spectroscopy was particularly relevant to the characterization of the Cu(ii ) complexes of both macrocycles and to study the coordination chemistry of these ligands with Cu(ii ) ions.